Active heave compensated load transfer in marine overhead crane system through the use of distance sensor [electronic resource] - Lee, Frederick Yong Fung, 1989-; Zaini Ahmad; Fakulti Kejuruteraan Mekanikal (2013)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2013